PENGEMBANGAN MEDIA PEMBELAJARAN “PETUALANGAN SI DARAH MERAH” BERBASIS POWERPOINT UNTUK MENINGKATKAN KETERAMPILAN LITERASI MEMBACA SISWA KELAS V SD MUHAMMADIYAH NGUPASAN - Anggita Lestari; Urip Muhayat Wiji Wahyudi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Reading literacy is an important ability for elementary school students because it involves understanding information, identifying essential ideas, interpreting content, and drawing conclusions from texts. This study focused on developing an interactive PowerPoint learning medium entitled “Petualangan Si Darah Merah” (The Red Blood Cell’s Adventure) to support the improvement of reading literacy among fifth-grade elementary school students. The study applied a Research and Development (R&D) approach with the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation. The research was conducted at SD Muhammadiyah Ngupasan, Yogyakarta. Data were obtained through observation, interviews, questionnaires, and reading literacy tests. Product feasibility was determined through assessments by media and subject matter experts, while practicality was examined through teacher and student responses. Product effectiveness was evaluated using pretest and posttest results supported by normality, homogeneity, independent sample t-test, and N-Gain analyses. The validation results indicated that the media expert assessment reached 95% and the subject matter expert assessment reached 100%, both categorized as highly feasible. The practicality assessment resulted in 88.3% from the teacher and 87.5% from students, indicating a very practical category. In the field trial, the experimental class increased from 64.50% in the pretest to 81.92% in the posttest, whereas the control class increased from 56.29% to 71.63%. The independent sample t-test produced a significance value of 0.002, indicating a significant difference between the two groups. The mean N-Gain percentage was 57.51% for the experimental class and 38.18% for the control class. These findings indicate that the “Petualangan Si Darah Merah” PowerPoint-based interactive learning medium is feasible and practical and provides sufficient effectiveness in supporting the reading literacy development of fifth-grade students.